Measurement of the τ lepton polarization in Z boson decays in proton-proton collisions at √s=13 TeV - Hayrapetyan,A; Tumasyan,A; Adam,W; Andrejkovic,JW; Bergauer,T; Chatterjee,S; Damanakis,K; Dragicevic,M; Del,Valle AE; Hussain,PS; Jeitler,M; Krammer,N; et al. (The Journal of High Energy Physics, 2024)
The polarization of τ leptons is measured using leptonic and hadronic τ lepton decays in Z → τ +τ − events in proton-proton collisions at √s = 13 TeV recorded by CMS at theCERN LHC with an integrated luminosity of 36.3 fb−1. The measured τ − lepton polarization at the Z boson mass pole is Pτ (Z) = −0.144 ± 0.006 (stat) ± 0.014 (syst) = −0.144 ± 0.015,in good agreement with the measurement of the τ lepton asymmetry parameter of Aτ = 0.1439 ± 0.0043 = −Pτ (Z) at LEP. The τ lepton polarization depends on the ratio of thevector to axial-vector couplings of the τ leptons in the neutral current expression, and thus on the effective weak mixing angle sin2 θeffW, independently of the Z boson production mechanism. The obtained value sin2 θeffW = 0.2319 ± 0.0008(stat) ± 0.0018(syst) = 0.2319 ± 0.0019 is in good agreement with measurements at e+e− colliders.